2007
DOI: 10.1111/j.1742-1241.2007.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the baby-friendly hospital initiative on long-term breast feeding

Abstract: The aim of this study was to evaluate the effects of 'baby-friendly hospital initiative' (BFHI) on breast feeding. In the four consecutive months after BFHI in Gazi University Hospital (November 2002-February 2003), breast feeding status until the second year of life in 297 babies, born in the same hospital was compared with the values of 258 babies born before BFHI (November 2001-February 2002). The exclusive breast feeding rate in the first 6 months was higher in the babies born after BFHI. Cox regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…With these results, Çorum reached the proposed Healthy People 2010 goals of 63.0% of infants being exclusively breastfed at 3 months of age (27). In the other studies from Turkey exclusive breastfeeding rates were 34.3, 46, 53.7 and 60.9% at four months (12,23,25,28). Another study from Norway reported exclusive breastfeeding rate as 44% at four months and 7% at six months of age (29).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…With these results, Çorum reached the proposed Healthy People 2010 goals of 63.0% of infants being exclusively breastfed at 3 months of age (27). In the other studies from Turkey exclusive breastfeeding rates were 34.3, 46, 53.7 and 60.9% at four months (12,23,25,28). Another study from Norway reported exclusive breastfeeding rate as 44% at four months and 7% at six months of age (29).…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Çamurdan et al reported that Baby-Friendly Hospital Initiative movement did not affect the time of weaning (23). Also Bonuck et al observed similar rates of exclusive breastfeeding in the two groups and suggested that the intervention was not effective in helping women to breastfeed exclusively (24).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Turkey with 297 children born in a BFH revealed slightly better EBF rates of 97.4%, 76.1%, 53.7% and 9.3% at 15 days, 2, 4 and 6 months, respectively (7) . A study in Itaúna (MG), Brazil identified lower EBF rates of 62.6% at 1 month, 19.5% at 4 and 5.3% at 6 months (18) .…”
Section: Discussionmentioning
confidence: 97%
“…International research on the BFHI indicates that after its implementation there were increases in the initiation of BF (EBF) (3) , the BF rates during hospitalization (4) , EBF at the time of hospital discharge (5) , the duration of EBF (5)(6)(7) and total BF (6,8) , as well as decreases in gastric tract infections and atopic eczema (6) . Likewise, national studies conducted to date reveal an increased duration of EBF (9)(10)(11)(12)(13) and BF (10) and increased rates of EBF and total BF in children admitted to the Intensive Care Unit (14) .…”
Section: Introductionmentioning
confidence: 99%
“…En termes de niveau de preuve, les interventions fondées sur tout ou partie des dix conditions proposées par l'Unicef sont qualifiées du grade B (présomption scientifique), pour améliorer le taux d'allaitement à la sortie de la maternité et entraîner une augmentation de la durée de l'allaitement exclusif. Dans la littérature, cette efficacité de la démarche IHAB s'observe quelque soit le contexte socio-économique [3][4][5][6][7]. Une étude publiée en 2001 a également rapporté l'association entre l'instauration de la démarche IHAB et l'amélioration de certains indicateurs de santé : ainsi, les nouveau-nés des hôpitaux impliqués dans la démarche présentaient, en plus de l'augmentation des taux d'allaitement maternel à trois et six mois, une diminution du risque d'infection gastrointestinale (odds ratio [OR] = 0,6 ; IC 95 % = [0,4-0,91]) et du risque de dermatite atopique (OR = 0,54 ; IC 95 % = [0,31-0,95]), par rapport aux nouveau-nés des établisse-ments du même pays non engagés dans cette démarche [8].…”
Section: Introductionunclassified